2020
DOI: 10.1007/s10798-020-09604-y
|View full text |Cite
|
Sign up to set email alerts
|

Students’ knowledge of emerging technology and sustainability through a design activity in technology education

Abstract: The purpose of this study is to explore whether, and if so how, a design activity could encourage students to express and develop knowledge on emerging technology in relation to issues about sustainability. Several researchers have asserted that, in today’s technologically dependent society, it is important to be able to control technology and make informed decisions connected to technology. Design activities could make a significant contribution to technology education while students are developing their know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Att väva in framväxande teknik i en designprocess kan därför vara ett sätt att möjliggöra för elever att utveckla teknisk bildning om hur teknik kan bidra till hållbarhet. Det var utgångspunkten i en studie [1] där forskaren Johan Lind från Lunds universitet med kollegor undersökte hur elever i årskurs 8 diskuterade under en designuppgift. Resultaten visar att eleverna ofta gav uttryck för kunskap om framväxande tekniker och intog ett hållbarhetsperspektiv under designprocessen.…”
Section: Gunnar Höstunclassified
“…Att väva in framväxande teknik i en designprocess kan därför vara ett sätt att möjliggöra för elever att utveckla teknisk bildning om hur teknik kan bidra till hållbarhet. Det var utgångspunkten i en studie [1] där forskaren Johan Lind från Lunds universitet med kollegor undersökte hur elever i årskurs 8 diskuterade under en designuppgift. Resultaten visar att eleverna ofta gav uttryck för kunskap om framväxande tekniker och intog ett hållbarhetsperspektiv under designprocessen.…”
Section: Gunnar Höstunclassified
“…Creative problem-solving requires the formulation of solutions to common issues, including cognition and skills. Lind et al (2020) conducted a study on the students (aged 13-14) who negotiated and shared knowledge about technology as they interrelated with their fellow students. The study found that the students expressed knowledge about emerging technology and adopted a sustainability perspective while working in design activity.…”
Section: Design Activity As a Process Of Creative Learningmentioning
confidence: 99%
“…According to Nordlöf et al (2022), raising teachers' information literacy is essential to transforming teacher-student relationships and rethinking conventional teaching methods. Technology literacy is essential for teacher preparation, yet higher learning environments frequently do not offer enough resources to help students reach their full potential (Lind et al, 2022). The absence of integration of technological literacy in teacher education programs at the higher education level makes it difficult for future teachers to successfully use technological tools in their teaching (Alda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%